TMEM147 interacts with lamin B receptor, regulates its localization and levels, and affects cholesterol homeostasis - Christodoulou, Andri; Maimaris, Giannis; Makrigiorgi, Andri; Charidemou, Evelina; Lüchtenborg, Christian; Ververis, Antonis; Georgiou, Renos; Lederer, Carsten W.; Haffner, Christof; Brügger, Britta; Santama, Niovi (Journal of cell science, 2020)
The structurally and functionally complex endoplasmic reticulum (ER) hosts critical processes including lipid synthesis. Here, we focus on the functional characterization of transmembrane protein TMEM147, and report that it localizes at the ER and nuclear envelope in HeLa cells. Silencing of TMEM147 drastically reduces the level of lamin B receptor (LBR) at the inner nuclear membrane and results in mistargeting of LBR to the ER. LBR possesses a modular structure and corresponding bifunctionality, acting in heterochromatin organization via its N-terminus and in cholesterol biosynthesis via its sterol-reductase C-terminal domain. We show that TMEM147 physically interacts with LBR, and that the C-terminus of LBR is essential for their functional interaction. We find that TMEM147 also physically interacts with the key sterol reductase DHCR7, which is involved in cholesterol biosynthesis. Similar to what was seen for LBR, TMEM147 downregulation results in a sharp decline of DHCR protein levels and co-ordinate transcriptional decreases of LBR and DHCR7 expression. Consistent with this, lipidomic analysis upon TMEM147 silencing identified changes in cellular cholesterol levels, cholesteryl ester levels and profile, and in cellular cholesterol uptake, raising the possibility that TMEM147 is an important new regulator of cholesterol homeostasis in cells.This article has an associated First Person interview with the first author of the paper.
Gesehen am 10.06.2021
DOI funktioniert nicht